A SARS-CoV-2 Negative Antigen Rapid Diagnostic in RT-qPCR Positive Samples Correlates With a Low Likelihood of Infectious Viruses in the Nasopharynx - Corrêa, Isadora Alonso; Faffe, Débora Souza; Galliez, Rafael Mello; Gonçalves, Cássia Cristina Alves; Maia, Richard Araújo; da Silva, Gustavo Peixoto; Moreira, Filipe Romero Rebello; Mariani, Diana; Campos, Mariana Freire; Leitão, Isabela de Carvalho; de Souza, Marcos Romário; Cunha, Marcela Sabino; et al. (Frontiers in Microbiology, 2022)
SARS-CoV-2 transmission occurs even among fully vaccinated individuals; thus, prompt identification of infected patients is central to control viral circulation. Antigen rapid diagnostic tests (Ag-RDT) are highly specific, but sensitivity is variable. Discordant RT- qPCR vs Ag-RDT results are reported, raising the question of whether negative Ag-RDT in positive RT-qPCR samples could imply the absence of infectious viruses. To study the relationship between a negative Ag-RDT results with virological, molecular, and serological parameters, we selected a cross sectional and a follow-up dataset and analyzed virus culture, subgenomic RNA quantification, and sequencing to determine infectious viruses and mutations. We demonstrated that a positive SARS-CoV-2 Ag-RDT result correlates with the presence of infectious virus in nasopharyngeal samples. A decrease in sgRNA detection together with an expected increase in detectable anti-S and anti-N IgGs was verified in negative Ag-RDT / positive RT-qPCR samples. The data clearly demonstrates the less likelihood of a negative Ag-RDT sample to harbour infectious SARS-CoV-2 and consequently with a lower transmissible potential.